mPEG-PDLLA Micelles Potentiate Docetaxel for Intraperitoneal Chemotherapy in Ovarian Cancer Peritoneal Metastasis - Zhang, Yumei; Wang, Shunli; Duan, Xiaofan; Xu, Xiaoxiao; Gao, Yuan; Zhou, Jiuli; Xu, Xiaolin; Li, Jin (Frontiers in Pharmacology, 2022)
Ovarian cancer is the second most common cause of death from gynecological cancer in women. It’s usually diagnosed late and accompanied with peritoneal metastasis. For ovarian cancer with peritoneal metastasis, the advantage of intraperitoneal (IP) chemotherapy can maintain a high drug concentration in the abdominal cavity and reduce local systemic toxicity. In recent years, docetaxel (DTX) has shown a broad-spectrum anti-tumor activity against various malignant tumors, such as ovarian cancer with peritoneal metastasis. However, it has been limited in clinical application due toits poor water solubility, prone to hypersensitivity, fluid retention and varying degrees of neurotoxicity. In this study, we prepared methoxy-poly (ethylene glycol)- block-poly(D,L-lactide) (mPEG-PDLLA) micelles loaded with DTX and developed alternatives, less toxic and effective DTX formulation without Tween-80, and evaluated its pharmacokinetics in the abdominal cavity, also efficacy in ovarian cancer with peritoneal metastasis. The mean diameter of DTX-mPEG-PDLLA was about 25 nm, and the pharmacokinetics of Balb/c mice via IP showed that the plasma exposure of DTX-mPEG-PDLLA was about 4 times lower compared with DTX. Importantly, it was observed that DTX-mPEG-PDLLA was significantly more effective and prolonged the survival period in SKOV-3 ovarian cancer peritoneal metastasis model. Moreover, the apoptosis rate and G2/M cell cycle arrest are significantly increased in vitro. Based on these findings, it is expected that DTX-mPEG-PDLLA can enhance the efficacy aganist ovarian cancer peritoneal metastasis, while reducing toxic side effects, and has the potential to be used in the clinical treatment of more peritoneal metastatic cancer.